Pendampingan dan Asistensi Relawan Pajak Tax Center UNIBI dalam Pelaporan SPT PPh Orang Pribadi di KPP Pratama Sumedang - Kaca Dian Meila; Ridwan Taufik; Risma Handayani; Bagas Dwi Nugroho (Universitas Methodist Indonesia, 2025)
The Directorate General of Taxes has an annual work program called Domestic Tax Volunteers (RENJANI) aimed at increasing the contribution and involvement of third parties, namely tax centers. The UNIBI Tax Center has collaborated with the West Java I Regional Office of the Directorate General of Taxes for tax volunteer activities through students to provide assistance, outreach, and education related to taxation to enhance taxpayer compliance, with placements at the Pratama Tax Office in Sumedang. This activity uses a service learning approach combined with an individual approach, where 21 tax volunteers directly assist taxpayers on-site at KPP Pratama Sumedang in reporting the Annual Personal Income Tax Return using forms 1770 SS and 1770 S through e-filing. The results of the Community Service (PkM) activities show that taxpayers in the KPP Pratama Sumedang area are greatly helped and very supportive of the onsite assistance to help taxpayers in reporting the Annual Personal Income Tax Return forms 1770 SS & 1770 S using e-filing on the djponline website